FRENCH LESSONS WITH A COMMUNICATIVE TEACHING APPROACH - Khalimova Makhbuba Turakulovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
Communicative approach is the newest of the methods used in teaching French. It emphasizes the use of French in everyday life. The approach aims at making the learner proficient in oral and writing skills. The communicative approach is learner oriented and even employs the mother tongue to education difficulties in language learning. The teacher does not translate but asks questions to give the learners clues to the meaning of what will be presented. This paper explains the tenets of the communicative approach and compares it with some other approaches. Finally, some recommendations are given among which are that the serving teachers should be trained in the approach and teacher training institutions should include that approach in their methodology courses.